1987
DOI: 10.1111/j.2042-3306.1987.tb01370.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute renal failure in six horses resulting from haemodynamic causes

Abstract: Summary Six horses had been admitted to the hospital because of illness other than renal failure; diarrhoea, myositis, abdominal pain and/or suspected bacterial sepsis. Hypotension and disseminated intravascular coagulopathy were frequent findings in the horses. Abnormally high serum creatinine concentration and urine specific gravity of less than 1.022 were found in the horses with acute renal failure. Hyponatremia and hypochloraemia were the most common abnormal electrolyte findings. Pronounced hyperkalaemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 22 publications
1
27
0
4
Order By: Relevance
“…It is also noteworthy that in horses, kidney disease is typically associated with digestive and respiratory problems and may also be related to the nephrotoxicity of some medications administered at length (BAYLY; PARADIS; REED, 1980;DIVERS et al, 1987;1992;CUNILLERAS;HINCHCLIFF, 1999;BAYLY, 2000). Tabet et al (2005) reported that renal biopsy is a technique used to identify the injury, evolution and severity of renal diseases but may cause complications, such as subcapsular and retroperitoneal hematomas, renal lacerations and bleeding in the renal arteries and veins.…”
Section: Introductionmentioning
confidence: 99%
“…It is also noteworthy that in horses, kidney disease is typically associated with digestive and respiratory problems and may also be related to the nephrotoxicity of some medications administered at length (BAYLY; PARADIS; REED, 1980;DIVERS et al, 1987;1992;CUNILLERAS;HINCHCLIFF, 1999;BAYLY, 2000). Tabet et al (2005) reported that renal biopsy is a technique used to identify the injury, evolution and severity of renal diseases but may cause complications, such as subcapsular and retroperitoneal hematomas, renal lacerations and bleeding in the renal arteries and veins.…”
Section: Introductionmentioning
confidence: 99%
“…Wichtige Parameter zur Einschätzung der funktionellen Integrität des proximalen Tubulus sind die Größen der fraktionellen Clearance der einzelnen Elektrolyte (Divers 1987) und das Verhältnis von Urin-Gammaglutamyltransferase (GGT) zu Urin-Kreatinin. Die mit dem Harn ausgeschiedene GGT stammt aus dem Bürstensaum des proximalen Tubulus.…”
Section: Introductionunclassified
“…Diese wird beim Pferd hauptsächlich durch Hypovolämie bei Kolik oder Diarrhoe hervorgerufen (Grossman et al 1982;Seanor et al 1984;Divers et al 1987) und ist oft reversibel. Jedoch kann eine lang anhaltende Hypoperlusion schließlich zu einem irreversiblen ischämischen intrinsischen (renalen) ANV führen.…”
Section: Introductionunclassified
“…Akute lokale Hypoperfusion und Hypoxie können auch durch Verlegung der Tubuli mit Myoglobinausfällungen bei Myopathien bzw. mit Zelldetritus bei Pyelonephritis verursacht werden (Divers et al 1987;Divers et al 1992). Weiterhin kann das renale ANV auch im Zusammenhang mit Intoxikationen entstehen.…”
Section: Introductionunclassified
See 1 more Smart Citation